DMF (2,5-dimethylfuran) as a perspective of second generation biofuel in spark ignition engines - Biernat, Krzysztof; Dziołak, Paulina Luiza (Studia Ecologiae et Bioethicae, 2008)
One year ago there turned out the first scientific publications about obtain possibilities of 2,5 -dimethylfuran (DMF) straight from fructose, from raw materials like cellulose, starch or fruits. According to some sources, DMF could be use like oxygen fuel component, because of its properties. In th is article were discussed physical and chemical properties of DMF, and raw possibilities to DMF production as a second generation biofuel, there were also discussed possible technologies of DMF obtaining in “Wisconsin-Madison” technology. Besides there was performed an estimation of DMF application possibilities in present internal combustion engines.